INTERACTIVE WORKLOAD TRACKING SYSTEM - Han, Lin Zaw (IRC, 2020)
Tracking system that are being used in the companies are outdated and time consuming. By creating a dashboard, it will increase efficiency and reduce the workload and the workflow hinderance. Researches show that current workload tracking system are behind paywall and on average would cost 10$ per to use. This project aims to determine how to reduce those average and create an interactive tracking workload system. In order to get a good working interactive workload system, this project aims to achieve the objectives such to identify the importance of the employees by tracking their workload and to develop an interactive dashboard that will be able to track the employees. To achieve those objectives, I am aiming to follow the SDLC (Software Development Life Cycle) and waterfall model. And I have divided my project workflow into 4 parts which are research tools, database construction, front-end construction, and testing. The 4 divided covered as the SDLC and waterfall models that I have followed the methods to finish the project. The result of the project is the working interactive workload tracking system where the users can see their tasks and their tasks progress. And the manager or supervisor can also see their employee progress with the help of pie chart. The website and the interface will satisfy the importance of the employee progress and the employees’ workloads. 6